Lagu Slompret-slompret Sebagai Pemicu Trance Pada Penari Jaran Kepang Turonggo Seto - Irawan, Yusuf Rizki (Universitas Negeri Semarang, 2016)
There is always trance in the show of Jaran Kepang Turonggo Seto. Music is one of the way to become trance, it’s song Slompret-slompret. This research to purpose of; Describe forms of performance Jaran Kepang Turonggo Seto; Knowing how the process of trance the dancers Jaran Kepang Turonggo Seto; to know how the purpose of song Slompret-slompret. The conclusion is; the performing of Jaran Kepang Turonggo Seto consists of many factor, there is a story, dancer, dance property, costume, make up, dance, stage, sound system, and music illustration; before the trance is happen, the dancer of Jaran Kepang Turonggo Seto have to through of lelaku, sikap and ritual jamasan, it’s the adult dancer will; the fuction of the song Slompret-slompret use to medium dancer to trance. In the song have composition lyrics, composition, melody and garap ricikan.